Tobamovirus infection aggravates gray mold disease caused by Botrytis cinerea by manipulating the salicylic acid pathway in tomato - Gupta, Rupali; Leibman-Markus, Meirav; Weiss, Daniela; Spiegelman, Ziv; Bar, Maya (Frontiers in Plant Science, 2023)
Botrytis cinerea is the causative agent of gray mold disease, and infects more than 1400 plant species, including important crop plants. In tomato, B. cinerea causes severe damage in greenhouses and post-harvest storage and transport. Plant viruses of the Tobamovirus genus cause significant damage to various crop species. In recent years, the tobamovirus tomato brown rugose fruit virus (ToBRFV) has significantly affected the global tomato industry. Most studies of plant-microbe interactions focus on the interaction between the plant host and a single pathogen, however, in agricultural or natural environments, plants are routinely exposed to multiple pathogens. Here, we examined how preceding tobamovirus infection affects the response of tomato to subsequent infection by B. cinerea. We found that infection with the tobamoviruses tomato mosaic virus (ToMV) or ToBRFV resulted in increased susceptibility to B. cinerea. Analysis of the immune response of tobamovirus-infected plants revealed hyper-accumulation of endogenous salicylic acid (SA), upregulation of SA-responsive transcripts, and activation of SA-mediated immunity. Deficiency in SA biosynthesis decreased tobamovirus-mediated susceptibility to B. cinerea, while exogenous application of SA enhanced B. cinerea symptoms. These results suggest that tobamovirus-mediated accumulation of SA increases the plants' susceptibility to B. cinerea, and provide evidence for a new risk caused by tobamovirus infection in agriculture.